Decision on The Translation of Mandarin Song Lyrics 你要的爱 Into Indonesian by Yuni Shara in André Lefevere’s Perspective - Yogi Bagus Adhimas; Dhani Kristiandri; Fajar Sidiq Baehaqqi (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2023)
This study discusses how the process of translating literary works of Mandarin song lyrics into Indonesian. In the translation process there are many things that influence, from the meaning of the word itself, to the purpose of the translation. This study aims to determine the translation method in the case study of the song